Peroxisome Proliferator–Activated Receptor α Protects Renal Tubular Cells from Gentamicin-Induced Apoptosis via Upregulating Na(+)/H(+) Exchanger NHE1 - Chen, Cheng-Hsien (Mol Med, 2015)
Peroxisome proliferator–activated receptor (PPAR)-α is a transcription factor that has been reported to inhibit gentamicin-induced apoptosis in renal tubular cells. However, the antiapoptotic mechanism of PPARα is still unknown. In this study, we found that PPARα overexpression induced Na(+)/H(+) exchanger-1 (NHE1) expression in the rat renal tubular cells NRK-52E. Beraprost, a PPARα ligand, also increased NHE1 expression in the renal tubules in normal mice, but not in PPARα knockout mice. Chromatin immunoprecipitation assays revealed that two PPARα binding elements were located in the rat NHE1 promoter region. Na(+)/H(+) exchanger activity also increased in the PPARα-overexpressed cells. Flow cytometry showed that the PPARα-overexpressed cells were resistant to apoptosis-induced shrinkage. Cariporide, a selective NHE1 inhibitor, inhibited the antiapoptotic effect of PPARα in the gentamicin-treated cells. The interaction between NHE1 and ezrin/radixin/moesin (ERM) and between ERM and phosphatidylinositol 4,5-bisphosphate in the PPARα-overexpressed cells was more than in the control cells. ERM short interfering RNA (siRNA) transfection inhibited the PPARα-induced antiapoptotic effect. PPARα overexpression also increased the phosphoinositide 3-kinase (PI3K) expression, which is dependent on NHE1 activity. Increased PI3K further increased the phosphorylation of the prosurvival kinase Akt in the PPARα-overexpressed cells. Wortmannin, a PI3K inhibitor, inhibited PPARα-induced Akt activity and the antiapoptotic effect. We conclude that PPARα induces NHE1 expression and then recruits ERM to promote PI3K/Akt-mediated cell survival in renal tubular cells. The application of PPARα activation reduces the nephrotoxicity of gentamicin and may expand the clinical use of gentamicin.